2015
DOI: 10.1111/maec.12331
|View full text |Cite
|
Sign up to set email alerts
|

Epiphyte assemblages of the Mediterranean seagrassPosidonia oceanica: an overview

Abstract: This paper reviews the main studies dealing with epiphytes of both leaves and rhizomes of Posidonia oceanica, the main seagrass found in the Mediterranean Sea. A total of 660 epiphyte species has been recorded, including 430 on leaves and 437 on rhizomes. Of these, 205 are Rhodophyta, and 19 Tunicata. The epiphyte assemblages demonstrate a gradient of dissimilarity from west to east, with the eastern area being the most unlike the others. The differences can be attributed mostly to rare species that differ amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
60
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(71 citation statements)
references
References 142 publications
4
60
0
Order By: Relevance
“…Epiphytic foraminiferal populations usually respond to nutrient enrichment with a decrease in abundance, thus they may be useful indicators of ecosystem decline in subtropical-tropical, oligotrophic marine habitats (Richardson, 2006). Although these protozoans in surface sediments colonized by P. oceanica have been shown to be useful indicators to characterize a given environment in an integrated way (MateuVicens et al, 2014), no information is reported about the possible significant changes of foraminifers in leaf epiphytic assemblages colonizing disturbed meadows of P. oceanica (Piazzi et al, 2015). Therefore, further investigations should be carried out on the use of this taxon as bioindicator in epiphytic community studies on P. oceanica.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Epiphytic foraminiferal populations usually respond to nutrient enrichment with a decrease in abundance, thus they may be useful indicators of ecosystem decline in subtropical-tropical, oligotrophic marine habitats (Richardson, 2006). Although these protozoans in surface sediments colonized by P. oceanica have been shown to be useful indicators to characterize a given environment in an integrated way (MateuVicens et al, 2014), no information is reported about the possible significant changes of foraminifers in leaf epiphytic assemblages colonizing disturbed meadows of P. oceanica (Piazzi et al, 2015). Therefore, further investigations should be carried out on the use of this taxon as bioindicator in epiphytic community studies on P. oceanica.…”
Section: Discussionmentioning
confidence: 98%
“…In this regard, increases in the epiphyte biomass, differences in their spatial heterogeneity, shifts in species composition, morphological groups and main taxonomic groups have been observed under human disturbance regimes (Balata et al, 2007;Ben Brahim et al, 2010;Martínez-Crego et al, 2010;Piazzi et al, 2004Piazzi et al, , 2015Ruiz et al, 2001).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Biotic interactions, such as grazing and competition amongst sessile organisms, may be responsible for this small-scale variability (Alcoverro et al, 1997;Mazzella & Russo, 1989;Prado et al, 2007). The presence of rocky substrata close or interspersed with meadows may also constitute an important factor influencing smallscale patterns of distribution of epiphytic assemblages (Piazzi et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Epiphytes are known to be more sensitive to environmental changes than their plant hosts (Nesti, Piazzi, & Balata, ). For example, nutrient enrichment causes an increase in epiphyte biomass, changes in the invertebrate/macroalgae ratio and modifications to species composition (Piazzi, Balata, & Ceccherelli, and references within). Understanding the distribution of macroepiphytic species should be particularly helpful to design monitoring programs.…”
Section: Introductionmentioning
confidence: 99%